Semi-nomadism in southern Israel today - Berman, Mildred (Annals of the Association of American Geographers, 1967)
(Abstracts of the papers presented at the 62nd annual meeting of the Association of American Geographers, Toronto, Ontario, Canada, August 29–31, 1966)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1967ZD76400010 tex.unique-id: [object Object]
Keywords: dept.egm

Dimensions of east African cultures - Good, CM [Review] - Stolberg, I (Professional Geographer, 1967)
tex.unique-id: ISI:A1967ZE22600024
Keywords: dept.egm; ⛔ No DOI found